Short background on the relationship between the Vatican Law and Eastern Canon Law - SARAIS, ALESSIO (Prawo Kanoniczne, 2017)
Vatican Law is made up by a plurality of sources, belonging also to out- side legal systems: in the Vatican City State (VCS) Canon Law (Law of the Catholic Church) is the Law of the State as well, because the State is closely related to the Holy See. The text of Law June 7th, 1929, nr. II, which dealt with the sources of Law in the VCS, made an explicit reference only to the Codex Iuris Canonici (of the Latin Church) and to the Apostolic Constitutions. In 1983 Pope John Paul II issued a new Codex Iuris Canonici (CIC) for the Latin Church. In 1990 the same Pope issued the Codex Canonum Eccle- siarum Orientalium (CCEO). e new Vatican Law of October 1st, 2008, nr. LXXI, replaced the previous Law nr. II/1929: according to Art. 1 of this new Law, the whole Canon Law is a primary source of Vatican Law (art. 1, Law nr. LXXI/2008). erefore, in the VCS the Oriental Canon Law is also in force, i.e. not only the CCEO, but the whole Corpus Iuris Canonici of the Oriental Churches as well.